Democratic theory and comparative politics - Guillermo O'Donnell (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1999)
The present text is, basically, a revision of democratic theory from the perspective of its inadequacies for including into its scope many of the recently democratized countries, as well as some older democracies located outside of the Northwestern quadrant of the world. After warning that it is a first step in a larger and more ambitious endeavor, the paper begins by critically examining various definitions of democracy, especially those that, claiming to follow Schumpeter, are deemed to be minimalist, or procesualist. On this basis, a realistic and restricted, but not minimalist, definition of a democratic regime is proposed. After this step, the connections of this topic with several others are explored, including political, social, and welfare rights; the state, especially in its legal dimension; and some characteristics of the overall social context. The main grounding factor that results from these explorations is the conception of agency, especially as it is expressed in the legal system of existing democracies - although the effectiveness of this system and of its underlying conceptions of agency vary quite widely across cases. The approach of the text emphasizes legal and historical factors, while also tracing, in several comparative excursi, some important differences among various kinds of cases. The main conclusions are stated in several propositions, the major thrust of which entails an invitation toward a theoretically disciplined broadening of the analytical and comparative scope of contemporary democratic theory.
Keywords: 300